Effect of photochemical activation of hydrogen peroxide bleaching gel with and without TiO2 and different wavelengths - Taciana Marco Ferraz Caneppele; Carlos Rocha Gomes Torres; Adriana Chung; Edson Hidenobu Goto; Soraya Consolin Lekevicius (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the effect of photochemical activation of hydrogen peroxide (H2 O2 ) bleaching gel with different wavelengths. Methods: In the study, 80 bovine incisors were used, which were stained in 25% soluble coffee and divided in 4 groups. The initial color was measured with the Easy Shade spectrophotometer by CIE Lab. An experimental 35% H2 O2 bleaching gel was used, either with or without the presence of titanium dioxide (TiO2 ) pigment, associated with two light sources: G1 - Transparent Gel (TG) and no activation; G2 - Gel with TiO2 and activation with blue LED (l=470nm)\laser (Easy Bleach) appliance; G3 - Gel with TiO2 and activation with ultraviolet (l=345nm - UV); G4 - TG and activation with UV. Three applications of the gels were made for 10 min, and in each, 3 activations of 3 min, with interval of 30 s between them. The coloration was evaluated again and the variation in color perception (DE) was calculated. The data were submitted to one-way ANOVA and Tukey's test at 5% significance level. Results: There were significant differences between G1 and G4. The greatest "E value was observed in G4 (13.37). There was no statistically significant difference (p>0.05) between the groups 2, 3 and 4. Conclusions: The presence of TiO2 particules in the bleaching gel did not interfere at the bleaching results.